Microbial Community Composition and Functional Capacity in a Terrestrial Ferruginous, Sulfate-Depleted Mud Volcano - Tu, Tzu-Hsuan; Wu, Li-Wei; Lin, Yu-Shih; Imachi, Hiroyuki; Lin, Li-Hung; Wang, Pei-Ling (Frontiers in Microbiology, 2017)
Terrestrial mud volcanoes (MVs) are an important natural source of methane emission. The role of microbial processes in methane cycling and organic transformation in such environments remains largely unexplored. In this study, we aim to uncover functional potentials and community assemblages across geochemical transitions in a ferruginous, sulfate-depleted MV of eastern Taiwan. Geochemical profiles combined with 16S rRNA gene abundances indicated that anaerobic oxidation of methane (AOM) mediated by ANME-2a group coincided with iron/manganese reduction by Desulfuromonadales at shallow depths deprived of sulfate. The activity of AOM was stimulated either by methane alone or by methane and a range of electron acceptors, such as sulfate, ferrihydrite, and artificial humic acid. Metagenomic analyses revealed that functional genes for AOM and metal reduction were more abundant at shallow intervals. In particular, genes encoding pili expression and electron transport through multi-heme cytochromes were prevalent, suggesting potential intercellular interactions for electron transport involved in AOM. For comparison, genes responsible for methanogenesis and degradation of chitin and plant-derived molecules were more abundant at depth. The gene distribution combined with the enhanced proportions of 16S rRNA genes related to methanogens and heterotrophs, and geochemical characteristics suggest that particulate organic matter was degraded into various organic entities that could further fuel in situ methanogenesis. Finally, genes responsible for aerobic methane oxidation were more abundant in the bubbling pool and near-surface sediments. These methane oxidizers account for the ultimate attenuation of methane discharge into the atmosphere. Overall, our results demonstrated that various community members were compartmentalized into stratified niches along geochemical gradients. These community members form a metabolic network that cascades the carbon transformation from the upstream degradation of recalcitrant organic carbon with fermentative production of labile organic entities and methane to downstream methane oxidation and metal reduction near the surface. Such a metabolic architecture enables effective methane removal under ferruginous, sulfate-depleted conditions in terrestrial MVs.